Gel polymer electrolyte composition for lithium metal battery, gel polymer electrolyte for lithium metal battery, and lithium metal battery comprising the same

CN122931017APending Publication Date: 2026-10-16SK ON CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610421607.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-11-24
Filing Date
2026-04-01
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0003]然而,将为了诱导稳定的成膜而设计的凝胶聚合物电解质应用于锂金属电池时,电解质的离子传导特性与稳定成膜诱导能力之间必然形成反比例关系,相较于应用液体电解质的电池,可能表现出更低的寿命特性和容量的表达

Benefits of technology

根据本发明的锂金属电池用凝胶聚合物电解质组合物和凝胶聚合物电解质具有高离子电导率和锂离子传导特性,并且通过在负极界面形成稳定的膜,可以提高锂金属电池的稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122931017A_ABST
    Figure CN122931017A_ABST
Patent Text Reader

Abstract

The gel polymer electrolyte composition for a lithium metal battery of the embodiment of the present application comprises: a compound comprising 1 or more ether groups and 4 or more acrylate groups, a fluorine-based organic solvent, and a lithium salt. Accordingly, the ion conductivity and stability of the lithium metal battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a gel polymer electrolyte composition for lithium metal batteries, a gel polymer electrolyte, and a lithium metal battery comprising the same. Background Technology

[0002] In recent years, due to global warming caused by increased carbon dioxide emissions, the world is strengthening environmental regulations to achieve carbon neutrality. Consequently, the use of internal combustion engine vehicles is restricted, and many companies and research institutions are focusing on the development of electric vehicles. Furthermore, the importance of secondary batteries, which are related to the performance of electric vehicles (energy density, lifespan characteristics, safety, etc.), is increasingly prominent. However, the energy density of currently commercially available liquid electrolyte-based lithium secondary batteries has reached its limit, and in terms of commercial application, the use of flammable liquid electrolytes poses a high risk of fire and explosion. To address these energy density and safety issues, gel polymer electrolytes, with their quasi-solid form, have received widespread attention. However, most gel polymer electrolytes have significantly lower ionic conductivity at room temperature than liquid electrolytes, making practical application difficult. Representatively, gel polymer electrolytes are formulated as chemically thermally crosslinked electrolytes and physically crosslinked gel polymer electrolytes. Chemically thermally crosslinked gel polymer electrolytes can adjust the functional groups and crosslinking density according to the choice of crosslinking agent, thereby ensuring ionic conductivity close to that of liquid electrolytes. When a suitable crosslinking agent is selected in the crosslinking agent unit to adjust the functional groups of the gel polymer electrolyte, it has the advantage that the film composition formed on the positive / negative electrode surface during battery operation can be changed by altering the lithium solvation structure contained in the liquid electrolyte.

[0003] However, when gel polymer electrolytes designed to induce stable film formation are applied to lithium metal batteries, an inverse relationship inevitably forms between the electrolyte's ionic conductivity and its ability to induce stable film formation. Compared to batteries using liquid electrolytes, these may exhibit lower lifetime characteristics and lower capacity. Therefore, to simultaneously address the energy density and safety issues of lithium metal batteries, it is necessary to develop a gel polymer electrolyte that ensures ionic conductivity close to that of liquid electrolytes while inducing stable film formation. Summary of the Invention

[0004] (a) Technical problems to be solved One technical problem of the present invention is to provide a gel polymer electrolyte composition and a gel polymer electrolyte having improved ionic conductivity and stability.

[0005] One technical problem of the present invention is to provide a lithium metal battery with improved ionic conductivity and stability.

[0006] (II) Technical Solution The gel polymer electrolyte composition for lithium metal batteries according to the present invention comprises: a compound containing one or more ether groups and four or more acrylate groups, a fluorinated organic solvent, and a lithium salt.

[0007] In an exemplary embodiment, the compound comprising one or more ether groups and four or more acrylate groups may include at least one of dipentaerythritol hexaacrylate (DPHA) and dipentaerythritol pentaacrylate (DPPA).

[0008] In an exemplary embodiment, the compound comprising one or more ether groups and four or more acrylate groups may be dipentaerythritol hexaacrylate (DPHA).

[0009] In an exemplary embodiment, the fluorinated organic solvent may include at least one of fluoroethylene carbonate (FEC), methyl (2,2,2-trifluoroethyl) carbonate (FEMC), trifluorotoluene (TFT), 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), and difluorobenzene (DFB).

[0010] In an exemplary embodiment, the fluorinated organic solvent may include fluoroethylene carbonate (FEC), methyl (2,2,2-trifluoroethyl) carbonate (FEMC), or a combination thereof.

[0011] In an exemplary embodiment, the gel polymer electrolyte composition may further comprise a non-fluorinated linear carbonate compound.

[0012] In an exemplary embodiment, the gel polymer electrolyte composition may further comprise ethyl methyl carbonate (EMC).

[0013] In an exemplary embodiment, the lithium salt may comprise one or more anionic lithium salts containing nitrogen.

[0014] In an exemplary embodiment, the lithium salt may include lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and lithium difluoro(bis(oxalic acid)phosphate) (LiDFBP).

[0015] In an exemplary embodiment, the molar ratio of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) to lithium difluoro(bis(oxalic acid)phosphate) (LiDFBP) can be from 9:1 to 5:5.

[0016] In an exemplary embodiment, the lithium salt may further include at least one selected from lithium nitrate (LiNO3), lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluorooxalate borate (LiDFOB), lithium di(oxalate borate) (LiBOB), lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), and lithium perchlorate (LiClO4).

[0017] In an exemplary embodiment, based on the total weight of the gel polymer electrolyte composition for lithium metal batteries, the content of the compound containing one or more ether groups and four or more acrylate groups may be less than 5% by weight.

[0018] In an exemplary embodiment, based on the total weight of the gel polymer electrolyte composition for lithium metal batteries, the content of the compound containing one or more ether groups and four or more acrylate groups can be 1.5% by weight or more.

[0019] In an exemplary embodiment, the content of the fluorinated organic solvent may be from 50% to 95% by weight, based on the total weight of the gel polymer electrolyte composition for lithium metal batteries.

[0020] In an exemplary embodiment, the lithium salt content can be from 15% to 30% by weight, based on the total weight of the gel polymer electrolyte composition for lithium metal batteries.

[0021] In an exemplary embodiment, the gel polymer electrolyte for lithium metal batteries may include a compound comprising one or more ether groups and four or more acrylate groups.

[0022] The lithium metal battery according to the present invention includes: a lithium negative electrode; a positive electrode, the positive electrode being disposed opposite to the negative electrode; and a gel polymer electrolyte for the lithium metal battery, wherein the gel polymer electrolyte is disposed between the negative electrode and the positive electrode.

[0023] In an exemplary embodiment, the positive electrode may comprise a positive electrode active material, which may include materials selected from LiCoO2, Li(Ni)2, etc. x Co y Mn z O2(x+y+z=1), Li(Ni) x Co y Al z At least one of O2 (x+y+z=1), LiFePO4, and sulfur.

[0024] (III) Beneficial Effects The gel polymer electrolyte composition and gel polymer electrolyte for lithium metal batteries according to the present invention have high ionic conductivity and lithium-ion conduction characteristics, and the stability of lithium metal batteries can be improved by forming a stable film at the negative electrode interface.

[0025] The gel polymer electrolyte can be widely used in green technology fields such as electric vehicles, battery charging stations, and other battery-based solar and wind power generation. Furthermore, the lithium metal battery can be used in eco-friendly electric vehicles and hybrid vehicles to prevent climate change by suppressing air pollution and greenhouse gas emissions. Attached Figure Description

[0026] Figure 1 and Figure 2 To illustrate schematic plan views and schematic cross-sectional views of a lithium metal battery according to an exemplary embodiment.

[0027] Figure 3a and Figure 3b To compare the ionic conductivity and lithium-ion transference number (t) including activation energy of Example 1, Reference Example, Comparative Example 1, and Comparative Example 2. + The results of the evaluation.

[0028] Figures 4a to 4i The results are based on the results of compressive strength tests conducted in Example 1, Comparative Example 1, and Comparative Example 2 to measure flexibility.

[0029] Figure 5 The lithium NMR analysis results are for Example 1, Reference Example, Comparative Example 1, and Comparative Example 2.

[0030] Figure 6 The results are Raman analysis results for Example 1, Reference Example, Comparative Example 1, and Comparative Example 2.

[0031] Figure 7 The results are FT-IR analyses of the solvent (EMC:FEMC:FEC = 3:5:2 volume%), reference example, comparative example 1, comparative example 2, and example 1.

[0032] Figure 8 XPS analysis results of lithium metal batteries applied in Reference Example, Comparative Example 1, Comparative Example 2 and Example 1 are shown.

[0033] Figure 9 A graph showing the comparison results of the lifetime characteristics of lithium-NCM batteries using lithium electrodes from Reference Example, Comparative Example 1, Comparative Example 2, and Example 1.

[0034] Figure 10The diagram shows a comparison of leakage current of lithium-NCM batteries using the reference example and Example 1.

[0035] Figure 11a and Figure 11b The results are obtained by transmission electron microscopy (TEM) analysis, comparing the film thickness formed on the positive electrode surface of lithium-NCM batteries with lithium electrodes of the application reference example and Example 1 after charging and discharging.

[0036] Figures 12a to 12c The results are based on the analysis of the chemical structural changes of reference example, example 1, and dipentaerythritol hexaacrylate (DPHA).

[0037] Figure 13 This is a graph analyzing the current density variation according to the voltage range for the reference example and Example 1.

[0038] Figure 14 The XPS analysis results are for the lithium electrode surfaces of the reference example and Example 1.

[0039] Figure 15 These are TEM images showing the thickness of the positive electrode film in the reference example and Example 1.

[0040] Figure 16 The images shown are SEM analysis images of the reference example and Example 1.

[0041] Figure 17 A graph illustrating the charge-discharge performance of Example 1 based on the number of cycles.

[0042] Figure 18 The graphs show the changes in volume resistance and interface resistance during cyclic operation for Reference Example, Example 1, Comparative Example 1, and Comparative Example 2.

[0043] Figure 19 LSV diagrams are shown to illustrate the oxidative stability of the Reference Example, Example 1, Comparative Example 1, and Comparative Example 2.

[0044] Figures 20a to 20b The evaluation diagram shows symmetrical cells evaluated with different current densities and current quantities to assess the stability and durability of the electrolyte and lithium in the Reference Example, Example 1, Comparative Example 1, and Comparative Example 2. Detailed Implementation

[0045] Unless otherwise defined, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used in this description is merely for the effective description of specific embodiments and is not intended to limit the invention.

[0046] Unless otherwise indicated by the context, the singular form used in this specification may also mean including the plural form.

[0047] Unless otherwise specifically defined in this specification, when describing a layer, film, thin film, region, plate, or other part as being "on" or "above" other parts, this can include not only cases where it is "directly" on other parts, but also cases where other parts are interspersed therewith.

[0048] The term "A and / or B" in this specification may refer to a form that includes both A and B, or a form that selects only one of A and B.

[0049] In this specification, "A-based compound" can refer to a compound containing the functional group A and its derivatives.

[0050] In this specification, "polymer electrolyte" refers not only to an electrolyte in a completely solid state, but also to a "gel polymer electrolyte" that contains an electrolyte solution within a polymer-based electrolyte. For example, the gel polymer electrolyte may include gels in forms classified according to the preparation method. For instance, it may include forms where the electrolyte swells after the preparation of a polymer matrix (physical gel) or forms prepared by curing a composition of electrolyte and monomer mixtures (chemical gel).

[0051] Hereinafter, embodiments of the present invention will be described in more detail with reference to the accompanying drawings. However, the accompanying drawings in this specification are merely exemplary embodiments of the present invention and, together with the above description, serve to further understand the technical concept of the present invention. Therefore, the present invention should not be interpreted solely based on the content shown in the accompanying drawings.

[0052] A gel polymer electrolyte composition for lithium metal batteries according to an exemplary embodiment (hereinafter, also referred to as "gel polymer electrolyte composition") may comprise: a compound comprising one or more ether groups and four or more acrylate groups, a fluorinated organic solvent, and a lithium salt.

[0053] The compound containing one or more ether groups and four or more acrylate groups can be used as a crosslinking agent for the gel polymer electrolyte composition.

[0054] The compound containing one or more ether groups and four or more acrylate groups has a flexible chain structure by including ether groups and acrylate groups, thereby exhibiting high ionic conductivity similar to that of liquid electrolytes.

[0055] Furthermore, the acrylate groups contained in the structure of the compound comprising one or more ether groups and four or more acrylate groups can form a stable inorganic negative electrode surface film when applied to lithium metal batteries by inducing an aggregation reaction between lithium cations in the components of the liquid electrolyte and anions containing nitrogen and additives.

[0056] Furthermore, the compounds containing one or more ether groups and four or more acrylate groups, by including functional groups that have relatively weak interactions with lithium ions, make the migration of lithium ions easier, thereby exhibiting high lithium ion conductivity.

[0057] Therefore, the gel polymer electrolyte according to embodiments of the present invention can provide excellent lifetime characteristics and improved electrochemical stability.

[0058] In some embodiments, the compound comprising one or more ether groups and four or more acrylate groups may specifically comprise one or more but less than three ether groups, or specifically one or two ether groups. Furthermore, the compound comprising one or more ether groups and four or more acrylate groups may specifically comprise four or more but less than eight acrylate groups, or specifically four or more but less than seven acrylate groups, or specifically four or more but less than six acrylate groups, or specifically five or six acrylate groups.

[0059] In some embodiments, the molecular weight of the compound comprising one or more ether groups and four or more acrylate groups can be from 200 g / mol to 1000 g / mol, specifically from 300 g / mol to 700 g / mol, specifically from 350 g / mol to 600 g / mol, specifically from 352.5 g / mol to 578.56 g / mol.

[0060] In some embodiments, the compound comprising one or more ether groups and four or more acrylate groups may include at least one of dipentaerythritol hexaacrylate (DPHA) and dipentaerythritol pentaacrylate (DPPA).

[0061] In some embodiments, the compound comprising one or more ether groups and four or more acrylate groups may be dipentaerythritol hexaacrylate (DPHA).

[0062] When the compound containing one or more ether groups and four or more acrylate groups is dipentaerythritol hexaacrylate (DPHA), the carbonyl groups (C=O) contained in the acrylate groups of DPHA can further increase the lithium-ion transference number through interaction with lithium ions. Furthermore, by inducing the aggregation of liquid electrolyte components to change the solvation structure, a stable inorganic-based film (inorganic-rich interphase) is formed on the negative electrode surface, improving oxidation stability in the positive electrode, thereby further improving the lifespan characteristics (cycle life) of lithium metal batteries.

[0063] In some embodiments, the fluorinated organic solvent may include fluorinated carbonate compounds, fluorinated aromatic compounds, and fluorinated ether compounds. The fluorinated organic solvent may include at least one selected from fluoroethylene carbonate (FEC), methyl (2,2,2-trifluoroethyl) carbonate (FEMC), trifluorotoluene (TFT), 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), and difluorobenzene (DFB).

[0064] In some embodiments, the fluorinated organic solvent can be a fluorinated cyclic carbonate compound or a fluorinated linear carbonate compound, and more specifically, it can include a fluorinated cyclic carbonate compound. Therefore, lithium salts can be dissolved more easily.

[0065] In some embodiments, the fluorinated organic solvent may include fluoroethylene carbonate (FEC), methyl (2,2,2-trifluoroethyl) carbonate (FEMC), or a combination thereof.

[0066] The gel polymer electrolyte, by containing the aforementioned fluorine-based organic solvent, forms a stable inorganic film with lithium fluoride (LiF) as the main component at the lithium metal anode interface, and ensures high oxidation stability at the cathode interface, thereby simultaneously improving the battery's lifespan, safety, and ionic conductivity.

[0067] The gel polymer electrolyte composition may further comprise a non-fluorinated organic solvent, which may comprise a non-fluorinated carbonate compound, and the non-fluorinated carbonate compound may comprise a non-fluorinated linear carbonate compound or a non-fluorinated cyclic carbonate compound.

[0068] When the fluorinated organic solvent is a fluorinated cyclic carbonate compound, the non-fluorinated organic solvent can be a non-fluorinated linear carbonate compound. Therefore, lithium solubility and ionic conductivity can be adequately ensured simultaneously.

[0069] For example, the non-fluorinated linear carbonate compound may include dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate, ethyl propyl carbonate, dipropyl carbonate, methyl acetate, ethyl acetate, propyl acetate, etc. In some embodiments, the gel polymer electrolyte composition may contain the above-mentioned fluorinated and non-fluorinated organic solvents, specifically fluorinated cyclic carbonate compounds and non-fluorinated linear carbonate compounds, more specifically FEC and / or FEMC, and EMC.

[0070] In some embodiments, the gel polymer electrolyte composition may contain ethyl methyl carbonate (EMC).

[0071] In some embodiments, the lithium salt may comprise one or more anionic lithium salts containing nitrogen.

[0072] In some embodiments, the lithium salt may include lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and lithium difluoro(bis(oxalic acid))phosphate (LiDFBP).

[0073] The lithium salt, by comprising one or more anionic lithium salts containing nitrogen, can participate in the solvation structure of lithium ions and undergo reduction decomposition during charging, thereby forming lithium nitrides (e.g., Li3N) with high ionic conductivity on the lithium electrode surface. Therefore, the ionic conductivity of lithium metal batteries can be improved.

[0074] Specifically, the lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) has an N / S bond structure, which can improve ionic conductivity. The lithium difluoro(bis(oxalate)phosphate) (LiDFBP) can form a stable SEI through the phosphate ester structure of the oxalate group.

[0075] In some embodiments, the molar ratio of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) to lithium difluoro(bis(oxalic acid)phosphate) (LiDFBP) can be from 9:1 to 5:5.

[0076] By satisfying the above-mentioned range, the molar ratio of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) to lithium difluoro(bis(oxalic acid)phosphate) phosphate (LiDFBP) can increase the migration of lithium ions in the electrolyte and inhibit the growth of lithium dendrites, thus simultaneously improving the lifespan characteristics and electrochemical stability of lithium metal batteries.

[0077] In some embodiments, the lithium salt may further include at least one selected from lithium nitrate (LiNO3), lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluorooxalate borate (LiDFOB), lithium di(oxalate borate) (LiBOB), lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), and lithium perchlorate (LiClO4).

[0078] In some embodiments, the content of the compound containing one or more ether groups and four or more acrylate groups may be less than 5% by weight, based on the total weight of the gel polymer electrolyte composition for lithium metal batteries.

[0079] In some embodiments, the content of the compound containing one or more ether groups and four or more acrylate groups may be 1.0% by weight or more, based on the total weight of the gel polymer electrolyte composition for lithium metal batteries.

[0080] In some embodiments, the content of the compound comprising one or more ether groups and four or more acrylate groups may be from 1.0% to 3% by weight, based on the total weight of the gel polymer electrolyte composition for lithium metal batteries.

[0081] When the content of the compound containing one or more ether groups and four or more acrylate groups meets the above range, the cross-linking reaction within the gel polymer electrolyte composition can be carried out uniformly, thereby ensuring a balance between mechanical stability and ionic conductivity.

[0082] In some embodiments, the content of the fluorinated organic solvent may be from 50% to 95% by weight, based on the total weight of the gel polymer electrolyte composition for lithium metal batteries.

[0083] When the content of the fluorinated organic solvent meets the above range, the curing degree of the gel polymer electrolyte and the migration of lithium ions can be improved, thereby improving the safety and ionic conductivity of lithium metal batteries.

[0084] In some embodiments, the lithium salt content may be from 15% to 30% by weight, based on the total weight of the gel polymer electrolyte composition for lithium metal batteries.

[0085] When the content of the lithium salt meets the above range, the conductivity and interface stability of lithium ions can be improved, thereby improving the ionic conductivity, charge-discharge efficiency and cycle life of lithium metal batteries.

[0086] The gel polymer electrolyte for lithium metal batteries according to the present invention (hereinafter, also simply referred to as "gel polymer electrolyte") may include compounds comprising one or more ether groups and four or more acrylate groups. The compounds comprising one or more ether groups and four or more acrylate groups included in the gel polymer electrolyte are as described above.

[0087] In some embodiments, the ionic conductivity of the gel polymer electrolyte can be 2.6 × 10⁻⁶. -3 The ionic conductivity of the gel polymer electrolyte can be above S / cm. For example, the ionic conductivity of the gel polymer electrolyte can be 10 × 10⁻⁶. -3 Below S / cm.

[0088] Typically, the ionic conductivity of gel polymer electrolytes may be lower than that of liquid electrolytes. However, the compounds containing one or more ether groups and four or more acrylate groups in the aforementioned gel polymer electrolytes have a flexible chain structure due to the inclusion of ether and acrylate groups, thus improving the ionic conductivity of lithium metal batteries.

[0089] In some embodiments, the gel polymer electrolyte may be a non-aqueous electrolyte that does not contain water.

[0090] In some embodiments, the compound comprising one or more ether groups and four or more acrylate groups included in the gel polymer electrolyte composition for lithium metal batteries can be used as a thermal crosslinking agent.

[0091] In some embodiments, the gel polymer electrolyte composition can be formulated as a thermosetting gel polymer electrolyte.

[0092] For example, the gel polymer electrolyte composition can be injected into a battery casing containing electrode components and then stored at about 70°C for 3 hours to induce a thermosetting reaction in situ, thereby forming a gel polymer electrolyte.

[0093] Figure 1 and Figure 2 The figures shown are a schematic plan view and a schematic cross-sectional view of a lithium metal battery according to an exemplary embodiment. Figure 2 For along Figure 1 A cross-sectional view taken from the I-I' line.

[0094] Figure 1 and Figure 2The lithium metal battery structure shown is schematic and the lithium metal battery structure according to this application is not limited thereto.

[0095] Reference Figure 1 and Figure 2 The lithium metal battery may include an electrode assembly 150, which includes a positive electrode 100 and a negative electrode 130. The electrode assembly 150 may be housed within a housing 160 together with the gel polymer electrolyte described above according to an exemplary embodiment. For example, the electrode assembly 150 may further include a gel polymer electrolyte 140 disposed between the positive electrode 100 and the negative electrode 130. Optionally, a separator may be further included between the positive electrode 100 and the negative electrode 130.

[0096] The positive electrode 100 may include a positive electrode current collector 105 and a positive electrode active material layer 110 disposed on at least one side of the positive electrode current collector 105.

[0097] In one embodiment, the lithium metal battery includes: a lithium negative electrode; a positive electrode disposed opposite to the negative electrode; and a gel polymer electrolyte for the lithium metal battery, the gel polymer electrolyte being disposed between the negative electrode and the positive electrode.

[0098] For example, the positive electrode current collector 105 may include stainless steel, nickel, aluminum, titanium, or alloys thereof. The positive electrode current collector may also contain aluminum or stainless steel surface-treated with carbon, nickel, titanium, or silver. The thickness of the positive electrode current collector is not limited thereto; for example, it may be from 10 μm to 50 μm.

[0099] For example, the positive electrode active material may contain compounds that can reversibly insert and deintercalate lithium ions.

[0100] In some embodiments, the positive electrode comprises a positive electrode active material, which may include materials selected from LiCoO2, Li(Ni) x Co y Mn z O2(x+y+z=1), Li(Ni) x Co y Al z At least one of O2 (x+y+z=1), LiFePO4, and sulfur.

[0101] In an exemplary embodiment, the positive electrode active material may comprise a lithium-transition metal oxide. For example, the lithium-transition metal oxide comprises nickel (Ni) and may further comprise at least one selected from cobalt (Co) or manganese (Mn).

[0102] For example, the lithium-transition metal oxide may have a structure represented by the following chemical formula A.

[0103] [Chemical Formula A] Li 1+a Ni 1-(x+y) Co x M y O2 In the Chemical Formula A, -0.05≤a≤0.15, 0.01≤x≤0.3, and 0.01≤y≤0.3 can be satisfied, and M may be one or more elements selected from Mn, Mg, Sr, Ba, B, Al, Si, Ti, Zr, or W.

[0104] In some embodiments, the positive electrode active material may include lithium metal phosphate oxide particles having a structure represented by the following Chemical Formula B.

[0105] [Chemical Formula B] Li w M x P y O 4+z In the Chemical Formula B, 0.9≤w≤1.2, 0.99≤x≤1.01, 0.9≤y≤1.2, and -0.1≤z≤0.1 can be satisfied, and M may be at least one selected from Fe, Ni, Mn, Ti, and V.

[0106] For example, in the Chemical Formula B, the M may be Fe, and the positive electrode active material may include a lithium iron phosphate-based (LFP) active material (e.g., LiFePO4).

[0107] In some embodiments, the positive electrode active material may include, for example, a Mn-rich based active material having a chemical structure or crystal structure represented by Chemical Formula C, a Li rich layered oxide (LLO) / Over Lithiated Oxide (OLO) based active material, or a Co-less based active material.

[0108] For example, the core of the positive electrode active material may include a chemical structure or crystal structure represented by the following Chemical Formula C.

[0109] [Chemical Formula C] p[Li2MnO3]·(1-p)[Li q JO2] In the Chemical Formula C, 0<p<1 and 0.9≤q≤1.2 can be satisfied, and J may include at least one element selected from Mn, Ni, Fe, Cr, V, Cu, Zn, Ti, Al, Mg, and B.

[0110] For example, the positive electrode active material can be dispersed in a solvent to prepare a positive electrode mixture. The positive electrode mixture can be coated onto the positive electrode current collector 105 and then dried and calendered to manufacture the positive electrode 100. The coating process can be performed by methods such as gravure coating, slot die coating, multilayer simultaneous die coating, embossing, doctor blade coating, dip coating, bar coating, casting, etc., and is not limited to these methods. The positive electrode mixture may further contain a binder, and optionally may further contain conductive materials and thickeners, etc.

[0111] Non-limiting examples of solvents used in the preparation of the cathode mixture include N-methyl-2-pyrrolidone (NMP), dimethylformamide, dimethylacetamide, N,N-dimethylaminopropylamine, ethylene oxide, tetrahydrofuran, etc.

[0112] The adhesive may include polyvinylidene fluoride (PVDF), vinylidene fluoride-co-hexafluoropropylene copolymer (poly(vinylidene fluoride-co-hexafluoropropylene)), polyacrylonitrile, polymethyl methacrylate, nitrile rubber (NBR), polybutadiene rubber (BR), styrene-butadiene rubber (SBR), etc. In one embodiment, the positive electrode adhesive may be a PVDF-based adhesive.

[0113] The conductive material can be added to improve the conductivity and / or the mobility of lithium ions or electrons in the positive electrode active material layer. For example, the conductive material may include carbon-based conductive materials such as graphite, carbon black, acetylene black, Ketjen black, graphene, carbon nanotubes, vapor-grown carbon fiber (VGCF), and carbon fibers, and / or metal-based conductive materials including tin, tin oxide, titanium oxide, perovskite materials (LaSrCoO3, LaSrMnO3, etc.).

[0114] The thickener may be, for example, carboxymethyl cellulose (CMC).

[0115] In some embodiments, the negative electrode 130 can be an electrode for a lithium metal battery. For example, the negative electrode can be lithium metal.

[0116] According to an exemplary embodiment, the negative electrode 130 may further include an electrode current collector 125. The lithium metal storage layer 120 may be disposed on at least one side of the electrode current collector 125.

[0117] The electrode current collector 125 may include gold, stainless steel, nickel, aluminum, iron, titanium, copper, or alloys thereof, for example, copper or copper alloys.

[0118] In one embodiment, a gel polymer electrolyte 140 may be disposed between the positive electrode 100 and the negative electrode 130.

[0119] Optionally, a separator may be provided between the positive electrode 100 and the negative electrode 130. The separator prevents electrical short circuits between the positive and negative electrodes and maintains ion flow. In one embodiment, the separator thickness may be from 10 μm to 20 μm.

[0120] The diaphragm may comprise a porous polymer membrane or a porous nonwoven fabric. The porous polymer membrane may comprise polyolefin-based polymers such as ethylene polymers, propylene polymers, ethylene / butene copolymers, ethylene / hexene copolymers, and ethylene / methacrylate copolymers. The porous nonwoven fabric may comprise high-melting-point glass fibers, polyethylene terephthalate fibers, etc. For example, the diaphragm may comprise polyethylene.

[0121] The membrane may also comprise a ceramic-based material. For example, inorganic particles may be coated on or dispersed within the polymer membrane to improve heat resistance.

[0122] The diaphragm may have a single-layer or multi-layer structure comprising the aforementioned polymer membrane and / or nonwoven fabric.

[0123] In one embodiment, the lithium metal battery may not include the separator. The gel polymer electrolyte essentially acts as a separator, preventing short circuits between the positive electrode 100 and the negative electrode 130. Furthermore, lithium ions can migrate between the positive electrode 100 and the negative electrode 130 through the gel polymer electrolyte.

[0124] In some embodiments, the area and / or volume of the negative electrode 130 can be larger than that of the positive electrode 100. Therefore, lithium ions generated from the positive electrode 100 can migrate smoothly to the negative electrode 130 without being deposited in the middle.

[0125] According to an exemplary embodiment, the battery cell may be defined by a positive electrode 100, a negative electrode 130 and a gel polymer electrolyte 140, and an electrode assembly 150 may be formed, for example, in the form of a jelly roll, by stacking multiple battery cells.

[0126] Optionally, the cell can be defined by a positive electrode 100, a negative electrode 130, a gel polymer electrolyte 140, and a separator. In some embodiments, the electrode assembly 150 may have a wound form formed by winding, stacking, z-folding, or stack-folding the positive electrode 100, the negative electrode 130, and the gel polymer electrolyte 140.

[0127] In one embodiment, the positive electrode 100, the negative electrode 130, and the gel polymer electrolyte 140 can be cut or separated layer by layer and then repeatedly stacked to form an electrode assembly.

[0128] For example, tabs (positive or negative) may protrude from the positive current collector 105 and the negative current collector 125 and extend to one side of the housing 160, respectively. The tabs may be fused to said side of the housing 160 and connected to electrode leads (positive and negative leads) extending to or exposed outside the housing 160.

[0129] For example, pouch-shaped shells, prismatic shells, cylindrical shells, coin-shaped shells, etc. can be used.

[0130] The electrode assembly 150 is housed together with the electrolyte in the housing 160, thereby defining a lithium secondary battery.

[0131] For example, the gel polymer electrolyte described above according to the exemplary embodiments can be used not only in the manufacture of lithium secondary batteries, but also in the manufacture of sodium secondary batteries, potassium secondary batteries, calcium secondary batteries, etc.

[0132] The embodiments of the present invention will be further described below with reference to specific experimental examples. The embodiments and comparative examples included in the experimental examples are only for illustrating the present invention and are not intended to limit the scope of the claims. Various changes and modifications can be made to the embodiments within the scope of the present invention and its technical concept, which is obvious to those skilled in the art, and such variations and modifications naturally fall within the scope of the claims.

[0133] Examples and Comparative Examples (1) Example 1 Li[Ni] will be used as the positive electrode active material 0.8 Co0.1 Mn 0.1 O2, carbon black (as a conductive material), and polyvinylidene fluoride (PVDF) (as a binder) were mixed in a weight ratio of 96:2:2 to prepare a slurry. The slurry was uniformly coated onto an aluminum foil with a thickness of 12 μm and vacuum dried at 110°C. The dried slurry was calendered to produce a product with a density of 3.2 g / cm³. 3 The positive pole.

[0134] Prepare an organic solvent in which fluoroethylene carbonate (FEC), methyl (2,2,2-trifluoroethyl) carbonate (FEMC) and methyl ethyl carbonate (EMC) are mixed in a volume ratio of 2:5:3.

[0135] The organic solvent is mixed with lithium salts to achieve a lithium salt concentration of 1M. The lithium salts are mixed with lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and lithium hexafluorophosphate (LiPF6) in a molar ratio of 4:6 to prepare a liquid electrolyte.

[0136] The liquid electrolyte is prepared by adding 3% by weight of dipentaerythritol hexaacrylate (DPHA) relative to the total weight of the gel polymer electrolyte composition and stirring.

[0137] The gel polymer electrolyte composition is injected into the cell, which consists of the positive electrode, a polyethylene (PE) membrane (13 μm thick), and a lithium metal negative electrode.

[0138] Subsequently, the injected gel polymer electrolyte composition is heat-treated at 70°C for 3 hours to form a gel polymer electrolyte inside the cell through an in-situ thermal crosslinking reaction, and a lithium metal battery including the gel polymer electrolyte is manufactured.

[0139] (2) Example 2 The gel polymer electrolyte and lithium metal battery of Example 2 were prepared by the same method as in Example 1, except that 1.5% by weight of the dipentaerythritol hexaacrylate (DPHA) was applied relative to the total weight of the gel polymer electrolyte composition.

[0140] (3) Example 3 The gel polymer electrolyte and lithium metal battery of Example 3 were prepared by the same method as in Example 1, except that 5% by weight of the dipentaerythritol hexaacrylate (DPHA) was applied relative to the total weight of the gel polymer electrolyte composition.

[0141] (4) Example 4 The gel polymer electrolyte and lithium metal battery of Example 4 were prepared by the same method as in Example 1, except that 7.5% by weight of the dipentaerythritol hexaacrylate (DPHA) was applied relative to the total weight of the gel polymer electrolyte composition.

[0142] (5) Reference Example Prepare an organic solvent in which fluoroethylene carbonate (FEC), methyl (2,2,2-trifluoroethyl) carbonate (FEMC) and methyl ethyl carbonate (EMC) are mixed in a volume ratio of 2:5:3.

[0143] The organic solvent is mixed with lithium salts to achieve a lithium salt concentration of 1M. The lithium salts are mixed with lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and lithium hexafluorophosphate (LiPF6) in a molar ratio of 4:6 to prepare a liquid electrolyte.

[0144] The liquid electrolyte is injected into the cell consisting of the positive electrode of Example 1, a polyethylene (PE) separator (13 μm thick) and a lithium metal negative electrode to manufacture a lithium metal battery.

[0145] (6) Comparative Example 1 The gel polymer electrolyte and lithium metal battery of Comparative Example 1 were prepared by the same method as in Example 1, except that 4% by weight of trimethylolpropane trimethacrylate (TMPTMA) was used instead of dipentaerythritol hexaacrylate (DPHA).

[0146] (7) Comparative Example 2 The gel polymer electrolyte and lithium metal battery of Comparative Example 2 were prepared by the same method as in Example 1, except that 5% by weight of ethoxylated trimethylolpropane triacrylate (ETPTA) was used instead of dipentaerythritol hexaacrylate (DPHA).

[0147] (8) Comparative Example 3 The gel polymer electrolyte and lithium metal battery of Comparative Example 3 were prepared by the same method as in Example 1, except that 3% by weight of ethoxylated trimethylolpropane triacrylate (ETPTA) was used instead of dipentaerythritol hexaacrylate (DPHA).

[0148] Experimental Example (1) Evaluation of ionic conductivity Ionic conductivity was measured using electrochemical impedance spectroscopy (EIS).

[0149] 80 μL of gel polymer electrolyte according to the examples, comparative examples and reference examples was loaded onto a polyethylene (PE) diaphragm, and an AC voltage was applied after contacting both sides with a stainless steel (Type 304) substrate. The impedance was measured in a symmetrical cell (frequency range: 1 Hz to 1 MHz, amplitude: 10 mV conditions).

[0150] The bulk resistance (R, Ω) of the electrolyte is calculated from the intersection of the semicircle or straight line in the high-frequency region of the impedance spectrum (Nyquist plot) with the real axis. The thickness (t, cm) and electrode cross-sectional area (A, cm²) of the gel polymer electrolyte sample are measured. 2 The ionic conductivity (σ, S / cm) is calculated according to Equation 2 below.

[0151] [Equation 2] σ=t / (R A) (In Equation 2, σ is the ionic conductivity (S / cm), t is the thickness (cm), and A is the cross-sectional area (cm²).) 2 R is the electrolyte resistance (Ω). Measurements were performed under various temperature conditions, thereby obtaining the temperature-dependent ionic conductivity characteristics of the electrolyte.

[0152] Furthermore, the lithium-ion transport number (t) was evaluated using a symmetrical cell composed of Li / electrolyte / Li, which was manufactured by loading 80 μL of a gel polymer electrolyte according to the examples, comparative examples, and reference examples onto a polyethylene (PE) separator and contacting Li metal electrodes on both sides. First, the initial interface resistance was measured by AC impedance analysis, followed by a polarization experiment with a constant DC voltage applied. The initial current after polarization and the steady-state current after polarization time were measured, and then the steady-state interface resistance was obtained again by AC impedance measurement. The above measurements were applied to the lithium-ion transport number (t) using the Bruce-Vincent formula in Equation 3. + ) calculation.

[0153] [Formula 3] In Equation 3, ΔV refers to the DC polarization voltage applied to the battery, I0 refers to the initial current after the DC voltage is applied, and I ss This refers to the steady-state current after the polarization time has fully elapsed. Furthermore, R0 refers to the initial interface resistance obtained through AC impedance analysis before polarization. ss It refers to the steady-state interface resistance obtained after polarization.

[0154] Figure 3a and Figure 3b To compare the ionic conductivity and lithium-ion transference number (t) including activation energy of Example 1, Reference Example, Comparative Example 1, and Comparative Example 2. + The results of the evaluation.

[0155] [Table 1] Refer to Table 1 and Figure 3a as well as Figure 3b It can be seen that, compared with the liquid electrolyte of the reference example, the gel polymer electrolytes of Examples 1 and 2 have lower ionic conductivity but significantly increased lithium-ion transference number. Furthermore, compared with Comparative Examples 1 and 2, the gel polymer electrolytes of Examples 1 and 2 have higher ionic conductivity and lithium-ion conductivity. This means that the gel polymer electrolytes according to the examples improve the selective mobility of lithium ions, alleviate the ion concentration deviation at the negative electrode interface, and thus improve the battery life and stability. Furthermore, through... Figure 3a The activation energy was calculated using the Arrhenius plot obtained by logarithmizing the ionic conductivity values ​​based on temperature as shown in Table 1. Comparing Comparative Example 1, Comparative Example 2, and Example 1, the activation energy of Example 1 was confirmed to be 0.18 eV, exhibiting the lowest level. This value is close to the activation energy of the liquid electrolyte in the reference example (0.16 eV), indicating that even after polymerization, the ion mobility is similar to that of the liquid electrolyte. Therefore, it can be confirmed that the electrolyte of Example 1 has properties beneficial to ion conduction within the electrolyte. Furthermore, as shown in Example 1, the lithium-ion transference number of the electrolyte composed of acrylate-based crosslinking agents is higher than that of the liquid electrolyte in the reference example. As shown in Comparative Example 2, when a large amount of ether groups are mixed in, the measured ion transference number is higher than that of the reference example. This confirms that, in addition to the type of functional group, its content may also affect the conductivity and lithium-ion transference number of the electrolyte.

[0156] (2) Evaluation of compressive strength Figure 4d For comparison example 1, Figure 4e For comparison example 2, Figure 4f The results show the results of the flexibility measured by compression strength test using the gel polymer electrolyte of Example 1 as the object.

[0157] Flexibility measurements were performed at room temperature (25°C) under a constant load, measuring stress based on strain rate. The modulus of the gel polymer electrolytes prepared from each precursor was measured after thermosetting, and the reciprocal of this value was taken to compare compliance values. The analytical apparatus used was an NX-10 (in the glove box, Park Systems, Korea), with scan sizes of 10 μm × 10 μm and 2 μm × 2 μm.

[0158] Reference Figures 4a to 4i It was confirmed that, compared to Comparative Example 1, Comparative Example 2 and Example 1, which contain ether groups, exhibited higher flexibility.

[0159] This means that the polymer chains have high degrees of freedom (flexibility) at room temperature and excellent recovery of deformation. Furthermore, it is known that the increased flexibility of this polymer component is directly related to the improved ion mobility within the gel polymer electrolyte.

[0160] (3) Lithium NMR analysis Figure 5 The lithium NMR analysis results are for Example 1, Reference Example, Comparative Example 1, and Comparative Example 2. (Refer to...) Figure 5 When comparing the reference example and Example 1, it can be confirmed that, compared to the reference example, in Comparative Example 1, Comparative Example 2 and Example 1, which contain acrylate groups, the lithium NMR peak shifts to the up-field direction.

[0161] This can be explained by the fact that when using a gel polymer electrolyte containing acrylate groups, lithium ions and solvent molecules undergo a kind of aggregation (ion-solvent aggregation) within the electrolyte. Therefore, it can be seen that, as in Comparative Example 1 and Example 1, using a gel polymer electrolyte with a high content of acrylate groups can more advantageously form the interaction and aggregation phenomenon between lithium salt and solvent components within the electrolyte.

[0162] (4) Raman analysis of electrolytes Figure 6 (a) is a reference example, (b) is comparative example 1, (c) is comparative example 2, and (d) is the Raman analysis result of the electrolyte of example 1.

[0163] The analysis results confirmed that, compared to the reference example, when the gel polymer electrolytes of Comparative Example 1 and Example 1 were used, an aggregate-type solvation structure was formed in the form of lithium ions and anions.

[0164] This means that the higher the proportion of acrylate functional groups in the polymer chain of the gel polymer electrolyte, the stronger the interaction between lithium ions and anions, and the more densely lithium ions exist in the electrolyte.

[0165] On the other hand, when the ether content is too high, the aggregation between electrolyte components is suppressed, and lithium ions tend to be relatively freely distributed.

[0166] Therefore, it can be confirmed that the gel polymer electrolyte according to Example 1, which contains more than 4 acrylate groups, is conducive to the formation of a quasi-aggregated (ion-solvent aggregated) structure between lithium ions and solvents and anions.

[0167] (5) FT-IR analysis of electrolytes Figure 7 The results are FT-IR analyses of the solvent (EMC:FEMC:FEC = 3:5:2 volume%), Reference Example, Comparative Example 1, Comparative Example 2, and Example 1. These results are based on the FT-IR analyses of the electrolytes of Reference Example, Comparative Example 1, Comparative Example 2, and Example 1 compared to the solvent (EMC:FEMC:FEC = 3:5:2 volume%) without lithium binding. The analysis shows that, compared to the Reference Example, Comparative Example 1 and Example 1, with their higher proportion of acrylate groups, exhibit higher binding rates of fluoroethylene carbonate (FEC) in the lithium solvated structure.

[0168] (6) XPS Analysis Figure 8 XPS analysis results of F 1s and N 1s on the lithium electrode surface were obtained after running the lithium metal batteries of Reference Example, Comparative Example 1, Comparative Example 2, and Example 1 for 20 cycles. The analytical apparatus used was K-alpha plus (Thermo Scientific, USA). The analytical conditions were as follows.

[0169] X-ray: Al Kα (1486.6 eV) 12 keV / 6 mA - Beam size: 400μm Pass Energy (eV) - Full spectrum scan (Survey Scan): 200 - Narrow Scan: 50 - Energy Step Size (eV) - Full spectrum scan: 1.0 - Narrow spectrum scan: 0.1 - Valence Scan: 0.05 -Sputter conditions (Etch) Sputter time: 90 seconds -Sputter Ion gun (Ar+): 1keV (Reference sputter rate (based on SiO2): 100nm / 1444s) Figure 8 (a) shows the spectrum of the lithium anode surface obtained in a lithium metal battery using the liquid electrolyte of the reference example. When compared with the undecomposed anions in the F 1s spectrum, it can be confirmed that the degree of formation of LiF components is relatively similar. In addition, a small amount of Li3N component was observed in the N 1s spectrum from the source of undecomposed anions.

[0170] Figure 8 (b) shows the XPS spectrum of the electrode obtained in a lithium metal battery using the gel polymer electrolyte of Comparative Example 1. Figure 8 (d) shows the XPS spectrum of the electrode obtained in a lithium metal battery using the gel polymer electrolyte of Application Example 1. In this case, it can be confirmed that a significantly larger amount of LiF component is formed compared to the undecomposed anions in the F 1s analysis. Furthermore, in the N 1s spectrum, in addition to the Li3N component, lithium nitride oxide (LiN2) with ionic conductivity is also detected. x O y Additional inorganic film components, such as those found in Example 1 and Comparative Example 1, were introduced. These results indicate that when the gel polymer electrolytes of Example 1 and Comparative Example 1 are used, an inorganic-based, stable SEI layer is increased on the surface of the lithium metal electrode.

[0171] On the other hand, it was confirmed that in Comparative Example 2, due to the high ether content, the electrolyte was difficult to aggregate, resulting in a low amount of inorganic film formed and a low content of inorganic components on the surface. Therefore, it is shown that the gel polymer electrolyte (Example 1) with a high content of acrylate functional groups is beneficial for forming a stable inorganic-based SEI layer on the surface of the lithium metal electrode.

[0172] (7) Evaluation of capacity and lifetime characteristics Figure 9 A graph showing the comparison results of the lifetime characteristics of lithium-NCM batteries using lithium electrodes from Reference Example, Comparative Example 1, Comparative Example 2, and Example 1 is provided. The positive electrode loading of the lithium-NCM batteries is 19.8 mg / cm³. 2 Similarly, the charge and discharge test conditions are as follows: charging is carried out at a current density of 0.33C, and discharging is carried out at a current density of 1.0C.

[0173] Reference Figure 9 Compared to the Reference Example, Comparative Example 1, and Comparative Example 2, Example 1 exhibits superior cycle life characteristics. This demonstrates that the functional groups within the polymer composition of the gel polymer electrolyte used in Example 1 influence the composition of the negative electrode surface film (SEI), resulting in a more stable film and improved lithium-ion conductivity.

[0174] (8) Evaluation of oxidative stability Figure 10 To demonstrate the lithium-NCM battery with lithium electrodes in the application reference example and Example 1, the results of the leakage current experiment were used to evaluate the oxidation stability due to the electrolyte application.

[0175] The positive electrode loading of the lithium-NCM batteries is 19.8 mg / cm³. 2 Similarly, the leakage current test is conducted in the following manner.

[0176] After charging the battery to 4.2V using constant current, the voltage is increased by 0.1V every 10 hours within the range of 4.2V to 4.9V, and the resulting current is measured.

[0177] The result, such as Figure 10 As shown, Example 1 exhibited a significantly lower oxidation leakage current across the entire range compared to the reference example. This can be explained by the fact that when the gel polymer electrolyte of Example 1 is used, an aggregation effect (ion aggregation effect) occurs between the polymer chains and the lithium salt / solvent components within the electrolyte, thereby improving the oxidation stability of the battery.

[0178] Therefore, it was confirmed that the gel polymer electrolyte of Example 1 provides excellent oxidative stability, enabling the lithium-NCM battery to maintain stable electrochemical behavior even in the high voltage region during operation.

[0179] (9) TEM analysis Figure 11a and Figure 11b The TEM analysis results show a comparison of the film thickness formed on the positive electrode surface of lithium-NCM batteries with lithium electrodes of the application reference example and Example 1 after 70 cycles.

[0180] The positive electrode loading of the lithium-NCM batteries is 19.8 mg / cm³. 2Similarly, the charge / discharge test conditions were the same: charging was conducted at a current density of 0.33C, and discharging was conducted at a current density of 1.0C. After 70 cycles, the positive electrode in the discharge state was collected for TEM image analysis.

[0181] Figure 11a The analysis of the positive electrode surface of the battery using the liquid electrolyte in the reference example revealed that the thickness of the byproduct layer formed on the surface was approximately 97 nm to 166 nm. On the other hand, Figure 11b The results of the analysis of the positive electrode surface of the battery using the gel polymer electrolyte of Example 1 confirm that the amount of surface byproducts formed is significantly reduced.

[0182] This result means that when the gel polymer electrolyte of Example 1 is applied, the aggregation (ion aggregation) phenomenon occurring within the electrolyte suppresses the side reactions between the electrolyte components and the electrode, resulting in a reduction of decomposition byproducts formed on the positive electrode surface. Therefore, the gel polymer electrolyte according to the example can improve the electrode surface stability of lithium-NCM batteries during long-term operation.

[0183] (10) FT-IR analysis of electrolytes Figures 12a to 12c The results of the analysis of chemical structure changes in the reference example, Example 1 (GPE), and dipentaerythritol hexaacrylate (DPHA) are shown.

[0184] Specifically, Figure 12a The FT-IR analysis results of the liquid electrolyte of Reference Example (LE), the gel polymer electrolyte of Example 1, and dipentaerythritol hexaacrylate (DPHA) (cross-linker) are shown.

[0185] In the reference example, at 1700cm -1 No obvious absorption peaks were observed nearby, indicating that C=C double bonds are almost non-existent. On the other hand, dipentaerythritol hexaacrylate (DPHA) showed an absorption peak at 1700 cm⁻¹. -1 A strong absorption peak was observed nearby, indicating that dipentaerythritol hexaacrylate (DPHA) contains a C=C double bond. Compared to dipentaerythritol hexaacrylate (DPHA), the peak at 1700 cm⁻¹ in Example 1 was significantly higher. -1 The intensity of the nearby peaks decreased, which means that the cross-linking reaction consumed the C=C double bond.

[0186] Figure 12b To illustrate the NMR analysis results of the gel polymer electrolyte of Example 1, it was confirmed that the intensity of a specific hydrogen signal decreased over time (0 hours → 3.0 hours), indicating that the functional group was depleted through the crosslinking reaction.

[0187] Figure 12c A table showing the conversion rate of multifunctional acrylates according to curing time is provided. As shown in the figure, the conversion rate is calculated using the vinyl hydrogen (H) of the multifunctional acrylate. a H b H C )of 1 The conversion rate of the cured material was calculated using H NMR integral values. The conversion rate reached 99.3% after 1.5 hours of curing and 99.9% after 3 hours of curing. Therefore, it can be confirmed that the crosslinking reaction was substantially completed under these conditions.

[0188] (11) Analysis of current density variation Figure 13 A graph is shown to illustrate the analysis of the current density variation according to the voltage range for Reference Example (LE) and Example 1 (GPE).

[0189] according to Figure 13 Compared to the reference example, Example 1 exhibits stable current density characteristics over a wider voltage range. This can be attributed to the improved thermal and electrochemical stability of the gel polymer electrolyte composition according to Example 1 through crosslinking, and it can be confirmed that the gel polymer electrolyte according to the example maintains excellent stability even under high voltage conditions.

[0190] (12) XPS analysis of lithium electrode surface Figure 14 XPS analysis results of the lithium electrode surfaces of Reference Example (LE) and Example 1 (GPE) are shown. The analysis conditions are the same as those described in the XPS analysis in (6) above.

[0191] Figure 14 (a) and (c) are F 1s spectra, in the reference example LiF( The peak intensity of the reference example (685.0 eV) was significantly higher than that of Example 1. This means that when the liquid electrolyte (LE) of the reference example was used, more LiF was formed on the lithium surface due to the decomposition of LiPF6. On the other hand, the peak intensity of LiF in Example 1 (GPE) was relatively low, which means that the polymer matrix of the gel polymer electrolyte suppressed the excessive formation of LiF on the lithium surface.

[0192] Figure 14 (b) and (d) are P 2p spectra, in the reference example PF( 136.9 eV) and POF ( The peak at 135.5 eV appeared weaker, while a stronger peak of the PF bond was observed in Example 1. This result suggests that a stable inorganic film (SEI / CEI) based on the PF bond formed by the decomposition of the electrolyte is more developed when a gel polymer electrolyte is applied.

[0193] Therefore, the gel polymer electrolyte of Example 1 can suppress the accumulation of LiF and form a PF-based stable interface layer, thereby improving the chemical stability of the electrode-electrolyte interface.

[0194] (13) Transmission Electron Microscope (TEM) analysis of positive electrode film thickness Figure 15 The images are TEM images of the positive electrode film thickness. (a) shows the initial state, (b) shows the positive electrode film thickness after 20 cycles of the reference example, (c) shows the initial state of Example 1, and (d) shows the positive electrode film thickness after 20 cycles of Example 1.

[0195] It can be confirmed that the membrane formed in the reference example is thick and uneven, while it can be confirmed that a stable membrane was formed from the beginning in Example 1, and a uniform and stable membrane was still formed after 20 cycles.

[0196] (14) Scanning Electron Microscope (SEM) Analysis Figure 16 (a) shows a SEM image of the reference example, with a rough and uneven surface, and large cracks and clumps observed. (b) shows a SEM image of Example 1 after 20 cycles, which confirms that the surface is smooth and uniform.

[0197] (15) Evaluation of charge and discharge performance Figure 17 To illustrate the charge-discharge performance of Example 1 according to the number of cycles, a high capacity and stable operating voltage are shown during the initial formation step. Although a decrease in capacity is observed as charge-discharge cycles progress, a stable capacity is maintained over a long period, and a low rate of capacity degradation is shown. These evaluation results were measured under the following conditions: The battery used was a CR2032-type coin cell, and the positive electrode used was LiNi coated on an aluminum current collector. 0.8 Co 0.10 Mn 0.1 O2 (NCM811) (loading) 29.2 mg, Φ=14 mm). The amount of electrolyte is based on the E / C ratio, adding an amount equivalent to... 3.6gAh -1 The quantity was evaluated. The separator was a 9μm polyethylene membrane, and the negative electrode was a 20μm lithium foil (Φ=16mm). The battery was manufactured using a galvanostatic evaluation method, operating within a 3.0V to 4.3V range, undergoing a 0.1C rate charge / discharge formation process, followed by a 0.33C rate charge / discharge activation process. The evaluation cycle was then performed at a charge rate of 0.33C and a discharge rate of 1.0C. The evaluation equipment used was a WBCS 3000 and a WonATech system.

[0198] (16) Resistance variation analysis Figure 18 The resistance measurements obtained after each cycle were performed using a potentiostat at room temperature, with an evaluation frequency of 1.0 mHz to 1.0 MHz and an amplitude of 5 mV. Figure 18 (a) shows the volume resistance (R) of Example 1, Comparative Example 1 (TMPTMA GPE), Comparative Example 2 (ETPTA GPE), and Reference Example according to cyclic operation. 本体(bulk) ), Figure 18 (b) shows the SEI layer resistance (R) SEI ) and charge transfer resistance (R ct (The graph shows the changes.) Figure 18 (a) shows the total bulk resistance generated when current flows inside the battery. It can be confirmed that Example 1, Comparative Example 1, and Reference Example all show a small level of bulk resistance difference in the initial stage, but Comparative Example 2 shows a significant increase in bulk resistance with increasing cycle number. This is explained as a result of low lithium-ion conductivity and high activation energy. Figure 18 (b) shows R ct It can be confirmed that the reference example initially showed a low resistance, but the resistance increased sharply with the increase of the number of cycles, while Example 1 maintained a constant and stable resistance from the beginning. On the other hand, the batteries using polymer electrolytes of Comparative Examples 1 and 2, which used other crosslinking agents with poor electrochemical properties, showed a significant increase in resistance with repeated cycling due to the degradation of membrane properties or lower charge transfer characteristics.

[0199] (17) Analysis of the size of the gel polymer electrolyte mesh Figures 4a to 4iTo measure the diffusion coefficient of the gel polymer electrolytes in Comparative Examples 1, 2, and 1, using the light scattering multi-point analysis function of a zeta potentiometer (ELSZneo, Otsuka, South Korea), and substituting the values ​​into the relationship between Brownian motion particle size and diffusion coefficient (Stokes-Einstein equation), the mesh size values ​​of each gel polymer were obtained and compared. The average value (D, m) of the diffusion coefficient measured by multi-point analysis was then obtained. 2 After substituting the values ​​that satisfy the Boltzmann constant, temperature, viscosity, etc., the effective radius (r, m) of the gel polymer mesh is obtained according to the following equation 4 (Stokes-Einstein equation).

[0200] [Formula 4] (In Equation 4, K) B Boltzmann constant (1.380649 × 10⁻⁶) -23 J / K), T is the absolute temperature (K), and η is the solvent viscosity (Pa·s). The preparation process for evaluation was as follows: 2 mL of the precursor of each gel polymer electrolyte was added to a 5 mL cuboid quartz tube, followed by a thermal cross-linking reaction at 70°C for 3 hours, after which measurements were taken. The measurement range was based on 5.0 mm along the x-axis, with three measurements taken at 0.5 mm intervals along the z-axis, and the average of the results was used as the diffusion coefficient. (Reference) Figures 4a to 4i hour, Figure 4a For comparison example 1, Figure 4b For comparison example 2, Figure 4c As shown in Example 1, it can be confirmed that gel polymer electrolytes using different crosslinking agents have the following characteristics: the larger the molecular weight of the crosslinking agent, the larger the mesh size. This is believed to be due to the difference in distance between the crosslinking points and the center of the crosslinking agent, and it is known that the larger the gel polymer mesh size, the more it helps to improve ionic conductivity when the gel polymer is used as an electrolyte. Furthermore, the multi-point analysis results show that, regardless of position, similar diffusion coefficient values ​​are observed within the error range when forming gel polymer electrolytes. This similarity of diffusion coefficients in the same gel polymer electrolyte suggests a result of ensuring the homogeneity of the gel polymer electrolyte.

[0201] (18) Comparative analysis of glass transition temperatures of gel polymer electrolytes Figure 4g For comparison example 1, Figure 4h For comparison example 2, Figure 4iThe results show the glass transition temperatures of each polymer, using the gel polymer components of Example 1 as the target. The analytical apparatus used was a DSC 2500 (TA Instruments, Korea). The analytical conditions were as follows: Equilibrate: -80.00°C; Isothermal: 5.0 min; Ramp 10.00°C / min to 400.00°C; Equilibrate: -80.00°C; Isothermal: 5.0 min; Ramp 10.00°C / min to 400.00°C. Figure 4g The Tg value of polymers containing only acrylate groups is shown to be 79.4°C above room temperature; on the other hand, the Tg value of polymers containing ether groups... Figure 4h and Figure 4i The Tg values ​​were shown to be -59.9℃ and -33.4℃, respectively, thus confirming the difference in the physical properties of the polymers. This result is interpreted as being due to differences in the number of functional groups in the polymers or the chain flexibility of the polymers, and can be explained by relating it to differences in the ionic conductivity of the gels during polymerization.

[0202] (19) Comparative analysis of the oxidative stability of liquid electrolytes and gel polymer electrolytes Figure 19 The oxidative stability was measured by linear sweep voltammetry (LSV).

[0203] Eighty μL of the gel polymer electrolyte according to Examples 1, 1 Comparative Example 1, 2 Comparative Example 2, and Reference Example was loaded onto polyethylene (PE). A stainless steel (SUS, 304) substrate was used as the working electrode, and a Li negative electrode was used as both the counter and reference electrodes in contact. A voltage was then applied in one direction (oxidation potential) through the electrodes on both sides of the sample, and the current change was analyzed to measure the impedance (voltage range: 3.0-6.0 V, scan rate: 1.0 mV / sec). In the LSV results, a current of 0.01 mA / cm² was generated. -2 This serves as a benchmark for evaluating oxidative stability.

[0204] (20) Electrolyte suitability evaluation for lithium-ion symmetric cells Figures 20a to 20b The method of evaluating symmetrical cells uses lithium / lithium symmetrical electrodes as two-sided electrodes, applies specific current densities and current quantities, observes the deposition / desorption stability of lithium, and measures the overvoltage change based on the side reactions between the electrolyte and the electrodes.

[0205] Eighty μL of a gel polymer electrolyte according to Example 1, Comparative Example 1, Comparative Example 2, and Reference Example was loaded onto polyethylene (PE), and the electrolyte was stacked between two Li metal electrodes (working electrode and counter electrode) to form a symmetrical cell. Preset current densities and current quantities were applied through the electrodes on both sides of the sample, and voltage changes were analyzed. Figure 20a Set to 0.5mAcm -2 Current density, 1.0 mAh / cm³ -2 The results were evaluated after measuring the current. Figure 20b Set to 1.5mAcm -2 Current density, 1.5 mAh / cm³ -2 The results were evaluated after measuring the current. The evaluation equipment used was WBCS 3000 and WonATech equipment.

Claims

1. A gel polymer electrolyte composition for lithium metal batteries, comprising: a compound containing one or more ether groups and four or more acrylate groups, a fluorinated organic solvent, and a lithium salt.

2. The gel polymer electrolyte composition for lithium metal batteries according to claim 1, wherein, The compound comprising one or more ether groups and four or more acrylate groups includes at least one of dipentaerythritol hexaacrylate (DPHA) and dipentaerythritol pentaacrylate (DPPA).

3. The gel polymer electrolyte composition for lithium metal batteries according to claim 1, wherein, The fluorinated organic solvent includes at least one of fluoroethylene carbonate (FEC), methyl (2,2,2-trifluoroethyl) carbonate (FEMC), trifluorotoluene (TFT), 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), and difluorobenzene (DFB).

4. The gel polymer electrolyte composition for lithium metal batteries according to claim 1, wherein, The gel polymer electrolyte composition further comprises a non-fluorinated linear carbonate compound.

5. The gel polymer electrolyte composition for lithium metal batteries according to claim 1, wherein, The gel polymer electrolyte composition further comprises ethyl methyl carbonate (EMC).

6. The gel polymer electrolyte composition for lithium metal batteries according to claim 1, wherein, The lithium salt comprises one or more anionic lithium salts containing nitrogen.

7. The gel polymer electrolyte composition for lithium metal batteries according to claim 1, wherein, The lithium salts include lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and lithium difluoro(bis(oxalic acid))phosphate (LiDFBP).

8. The gel polymer electrolyte composition for lithium metal batteries according to claim 7, wherein, The molar ratio of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) to lithium difluoro(bis(oxalic acid)phosphate) (LiDFBP) is 9:1 to 5:

5.

9. The gel polymer electrolyte composition for lithium metal batteries according to claim 1, wherein, The lithium salt further includes at least one selected from lithium nitrate (LiNO3), lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluorooxalate borate (LiDFOB), lithium bis(oxalate borate) (LiBOB), lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), and lithium perchlorate (LiClO4).

10. The gel polymer electrolyte composition for lithium metal batteries according to claim 1, wherein, Based on the total weight of the gel polymer electrolyte composition for lithium metal batteries, the content of the compound containing one or more ether groups and four or more acrylate groups is less than 5% by weight.

11. The gel polymer electrolyte composition for lithium metal batteries according to claim 1, wherein, Based on the total weight of the gel polymer electrolyte composition for lithium metal batteries, the content of the compound containing one or more ether groups and four or more acrylate groups is 1.0% by weight or more.

12. The gel polymer electrolyte composition for lithium metal batteries according to claim 1, wherein, Based on the total weight of the gel polymer electrolyte composition for lithium metal batteries, the content of the fluorinated organic solvent is from 50% to 95% by weight.

13. The gel polymer electrolyte composition for lithium metal batteries according to claim 1, wherein, Based on the total weight of the gel polymer electrolyte composition for lithium metal batteries, the content of the lithium salt is from 15% to 30% by weight.

14. A gel polymer electrolyte for lithium metal batteries, comprising a compound containing one or more ether groups and four or more acrylate groups.

15. A lithium metal battery, comprising: Lithium anode; The positive electrode is positioned opposite to the negative electrode. as well as The gel polymer electrolyte for lithium metal batteries according to claim 14, The gel polymer electrolyte is disposed between the negative electrode and the positive electrode.